2004
DOI: 10.1128/iai.72.5.2513-2520.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monocytic Interleukin-12 Production byCandida albicansvia Selective Activation of ERK Mitogen-Activated Protein Kinase

Abstract: Our previous data demonstrated that live Candida albicans inhibits interleukin-12 (IL-12) production by human monocytes. Here we explored whether C. albicans inhibits IL-12 via a released factor and whether the inhibition is mediated via mitogen-activated protein kinase (MAPK) regulation. Supernatant fluids were obtained from cultured C. albicans (SC5314) as well as cultured Saccharomyces cerevisiae after 20 h of incubation. At 2 h postincubation of monocytes with heat-killed C. albicans (HKCA) (2:1) to stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…This IL-12 inhibitory effect was dependent on the viability of C. albicans, because both heat-killed C. albicans and C. krusei induced similar amounts of IL-12. Further studies showed that IL-12 inhibitory activity is due to the secretion of a glycoprotein (112) and signaling through the selective activation of extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MAPK) (102). However, the identities of this soluble glycoprotein and the receptor responsible for the IL-12 inhibition signaling are unknown.…”
Section: Evasion Of Candida From the Host Defense Mechanismsmentioning
confidence: 99%
“…This IL-12 inhibitory effect was dependent on the viability of C. albicans, because both heat-killed C. albicans and C. krusei induced similar amounts of IL-12. Further studies showed that IL-12 inhibitory activity is due to the secretion of a glycoprotein (112) and signaling through the selective activation of extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MAPK) (102). However, the identities of this soluble glycoprotein and the receptor responsible for the IL-12 inhibition signaling are unknown.…”
Section: Evasion Of Candida From the Host Defense Mechanismsmentioning
confidence: 99%
“…To determine whether the biofilmenhancing effect of PBMCs is specifically associated with the activation of these immune cells by C. albicans biofilms, we tested whether PBMCs activated by a nonbiofilm source can also enhance biofilm formation. The activation method selected was exposure to LPS, a method which has previously been used to activate PBMCs (4,40). Adherent PBMCs were activated with LPS, and the ability of this LPS-induced PBMC supernatant to influence the ability of C. albicans to form biofilm was then determined.…”
Section: Fig 4 Enhancement Of C Albicans Biofilm In the Presence Ofmentioning
confidence: 99%
“…To examine the interactions between host immune cells and Candida biofilms, PBMCs were extracted from peripheral blood as described previously (39,40). Briefly, the collected blood was diluted (1:1) with Hanks' balanced salt solution (HBSS; Mediatech Inc., Herndon, VA), and 30 ml of this diluted blood was layered on a Histopaque density gradient (Sigma-Aldrich, St. Louis, MO) and centrifuged at 1,500 rpm for 40 min at 24°C.…”
Section: Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we found that the downregulated genes were involved in mitogen-activated protein kinases (MAPKs) signaling pathway. MAPK is a family of serine/threonine kinases that participates in pathogen- (7) and human monocytes (8), which could promote the phagocytosis of C. albicans and inhibit IL-12 production. In addition, Dectin-1 has been reported to be one of the pattern recognition receptor in innate immune sensing of C. albicans (9).…”
Section: Discussionmentioning
confidence: 99%